Efek inhibisi ekstrak buah mangrove Sonneratia alba terhadap ekspresi tumor growth factor-beta 1 pada aorta abdominal tikus yang diinduksi aterosklerosis - Huriatul Masdar (Jurnal Kedokteran Syiah Kuala, 2022)
Various studies have proven the antioxidant content of Sonneratia alba fruit. Antioxidants are known to play an important role in inhibiting the formation of fibrotic tissue and atheromatous plaques in atherosclerosis, in which TGF- β1 expression plays an important role in the fibrosis process of atherosclerosis. This study aimed to examine the effect of Sonneratia alba mangrove fruit extract on the expression of TGF- β1 in atherosclerosis-induced rat aorta. A total of 18 male rats, aged 6-8 weeks with a body weight of 180-250 grams were used in this study, divided into the standard (S), positive control (P) and treatment group (T). Groups P and T were induced atherosclerosis in initiation phase by giving a high-fat diet 20 grams per day for three days. Group T was given Sonneratia alba mangrove fruit extract at a dose 500 mg/kg b.w/day for three days orally. TGF- β1 expression in rat abdominal aorta was assessed by immunohistochemical techniques and microscopic imaging was performed in fields of view. The percentage of area expressing TGF- β1 was assessed using ImageJ software. The results showed the average percentage of TGF- β1 expression in group P (17,3%) was higher than in group T (12,2%) and S (8,9%). Statistical analysis using One Way Anova test showed a significant difference between groups (p=0,000). Further analysis using Bonferroni test showed a significant difference in groups P and T (p=0,022), T and S (p=0,023) and Pand S (p=0,000). In conclusion, Sonneratia alba mengrove fruit extract was able to inhibit TGF- β1 expression in atherosclerosis-induced rat aorta in initiation phase.